3D printing: an emerging technology for sensor fabrication. Issue 4 (19th September 2016) - Bogue, Robert
Abstract : Purpose: This study aims to provide a technical insight into sensors fabricated by three-dimensional (3D) printing methods. Design/methodology/approach: Following an introduction to 3D printing, this article first discusses printed sensors for strain and allied variables, based on a diverse range of principles and materials. It then considers ultrasonic and acoustic sensor developments and provides details of a sensor based on 3D printed electronic components for monitoring food quality in real-time. Finally, brief concluding comments are drawn. Findings: Several variants of the 3D printing technique have been used in the fabrication of a range of sensors based on many different operating principles. These exhibit good performance and sometimes unique characteristics. A key benefit is the ability to overcome the limitations of conventional manufacturing techniques by creating complex shapes from a wide range of sensing materials. Originality/value: 3D printing is a new and potentially important sensor fabrication technology, and this article provides details of a range of recently reported developments.